Factors associated with leukorrhea symptoms among female adolescents in high school: A cross-sectional study - Heriani, Heriani (Lentera Perawat, 2025)
Background: Leukorrhea is a common reproductive health issue among female adolescents, yet many students lack adequate knowledge and appropriate hygiene practices needed to prevent pathological symptoms. Objective: This study aimed to identify factors associated with leukorrhea symptoms among female adolescents in high school. Methods: A cross-sectional analytical survey was conducted among 56 female students selected using simple random sampling from Grade 12 at SMA Negeri 1 OKU in 2024. Data were collected using a structured questionnaire assessing leukorrhea symptoms, knowledge level, age category, and personal hygiene behavior. Descriptive statistics and Chi-square tests were used to examine associations between variables, with a significance level of p < 0.05. Results: The prevalence of pathological leukorrhea was 30.4%. Knowledge, age, and personal hygiene behavior were significantly associated with leukorrhea symptoms. Adolescents with low knowledge were more likely to experience pathological leukorrhea (p = 0.002). Early adolescents demonstrated a higher prevalence of pathological symptoms compared with late adolescents (p = 0.000). Poor hygiene behavior was also significantly associated with increased leukorrhea symptoms (p = 0.019). Conclusion: Knowledge level, age category, and hygiene behavior are key determinants of leukorrhea symptoms among female adolescents. School-based reproductive health interventions should be strengthened to improve adolescent knowledge and hygiene practices to reduce the risk of pathological leukorrhea.